Internet (Google) and Pediatric Dermatology. 5 new functions that have to be known. - Cutrone, M.; Grimalt, R. (European Journal of Pediatric Dermatology, 2005)
Waiting for future changes, we should try to use the enormous amount of scientific news already present in the net in the best and most comfortable way. This report is aimed at presenting and commenting on to Pediatricians and Dermatologists some new functions of research already available free of charge on the net, but not much used by Physicians.